CWB Perilaku Kerja Kontraproduktif Karyawan : Systematis Literature Review (Slr) - refila yusra refila; Ahmaddin Ahmad Tohar (LPPM Universitas Abdurrab, 2026)
Counterproductive Work Behavior refers to intentional actions that harm the organization, involving unethical, illegal, or undesirable conduct. This study maps research on counterproductive work behavior through articles indexed in Scopus and published between 2020 and 2025, focusing on psychological perspectives. The PRISMA guidelines were used as the research framework, with an initial search identifying 1,349 articles, which were then filtered based on publication year, subject area, document type, thematic relevance, and geographical context. This process resulted in 56 articles, from which 37 focusing on psychological studies were selected for inclusion analysis. The findings indicate a significant increase in research trends in 2025, with a geographic concentration in China. This review highlights major research patterns and existing gaps, emphasizing the need for broader geographic coverage and more diverse methodological approaches for future research. These findings are expected to provide a strong foundation for developing theories and solutions to manage deviant behavior in the workplace.